INFORMATION SYSTEM FOR THE ADMISSION OF NEW STUDENT CANDIDATES FOR THE BIDIKSIBA SCHOLARSHIP PATHWAY POLYTEKNIK NEGERI MALANG - Kadek Suarjuna Batubulan; Ratih Indri Hapsari; Budi Harijanto; Ane Fany Novitasari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Bidikiba Program (Education Scholarships Around Bukit Asam) is a program of educational scholarships provided by PT Bukit Asam Tbk (PTBA) to students high school graduates or equivalent from underprivileged families around the operational area companies to be able to continue their education at university. Implementation of Bidikiba scholarship acceptance selection is still done manually registration process, selection exams, and ranking of prospective students. Registration This is done by recording prospective students using Excel and if any Changes or errors in prospective students' data must be reported to the admin make edits to the data. The system is expected to help resolve problems in the process of accepting prospective students for the Bidikiba scholarship programat Malang State Polytechnic.